Sonar 5 ignite! - Smithers, Brian (Thomson/Course Technology, 2006)
Start making music in SONAR 5 right away! In these pages you will find everything you need to demystify the deep and powerful functions of this popular program, regardless of your prior experience. SONAR 5 Ignite! provides beginners with the skills they need to start composing, editing, and arranging music. Learn how to set up your project, create tracks, edit MIDI and digital audio clips, and use virtual instruments. Wrap things up by learning how to use SONAR's effects plug-ins and surround-sound capabilities to create a great-sounding mix that's ready for CD or Web distribution. If you want to make music and you're looking for maximum-strength tools with a minimum learning curve, this book will have you jamming in no time!